2013
DOI: 10.1016/j.actpsy.2013.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of visual information regarding allocentric processing in haptic parallelity matching

Abstract: Research has revealed that haptic perception of parallelity deviates from physical reality. Large and systematic deviations have been found in haptic parallelity matching most likely due to the influence of the hand-centered egocentric reference frame. Providing information that increases the influence of allocentric processing has been shown to improve performance on haptic matching. In this study allocentric processing was stimulated by providing informative vision in haptic matching tasks that were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
57
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(72 citation statements)
references
References 36 publications
12
57
3
Order By: Relevance
“…These deviations have been observed in haptic parallelity tasks performed in different planes, like the (mid)horizontal plane (e.g. Kaas & Van Mier, 2006, Kappers, 1999Kappers & Koenderink, 1999;Newport, Rabb, & Jackson, 2002; Zuidhoek, Kappers, Van der Lubbe, & Postma, 2003;Van Mier, 2013), the frontoparallel plane (Hermens, Kappers, & Gielen, 2006;Volcic, Kappers, & Koenderink, 2007), the midsagittal plane (Kappers, 2002;2004), the threedimensional plane and for both unimanual and bimanual responses (Kappers & Koenderink, 1999;Kappers, 2002). A study by Fernández-Díaz and Travieso (2011) even found large and systematic deviations when the parallelity task was performed in rear peripersonal space (behind the back of the participant), with deviations clearly being influenced by the natural orientation of the hand.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…These deviations have been observed in haptic parallelity tasks performed in different planes, like the (mid)horizontal plane (e.g. Kaas & Van Mier, 2006, Kappers, 1999Kappers & Koenderink, 1999;Newport, Rabb, & Jackson, 2002; Zuidhoek, Kappers, Van der Lubbe, & Postma, 2003;Van Mier, 2013), the frontoparallel plane (Hermens, Kappers, & Gielen, 2006;Volcic, Kappers, & Koenderink, 2007), the midsagittal plane (Kappers, 2002;2004), the threedimensional plane and for both unimanual and bimanual responses (Kappers & Koenderink, 1999;Kappers, 2002). A study by Fernández-Díaz and Travieso (2011) even found large and systematic deviations when the parallelity task was performed in rear peripersonal space (behind the back of the participant), with deviations clearly being influenced by the natural orientation of the hand.…”
Section: Introductionmentioning
confidence: 93%
“…It has been found that performance deviated more from veridicality when the horizontal distance between the hands was increased and when oblique orientations had to be matched compared to cardinal orientations (e.g. Kaas & Van Mier, 2006;Kappers, 1999Kappers, , 20022003;Van Mier, 2013). Additionally, the magnitude of the deviations has been found to be influenced by task instruction (Kaas & Van Mier, 2006;Van Mier, 2013).…”
Section: Factors Affecting Parallelity Matchingmentioning
confidence: 98%
See 2 more Smart Citations
“…This illusory rotation was predicted from results of a parallelity experiment: if participants have to make a test bar located to their right parallel to a reference bar located to their left, the test bar is always rotated clockwise with respect to the reference bar, e.g. [2][3][4][5][6] (see also Figure 1). Kappers showed that this rotation gradually and systematically increased with distance [7].…”
Section: Introductionmentioning
confidence: 99%